CONTRIBUTION OF THE CONCEPT OF TOTAL DEFENCE TO STATE’S RESILIENCE IN EMERGENCY SITUATIONS - Banjac, Nikola (The Policy of National Security, 2024)
Contemporary challenges, risks and threats to the security of the Republic of Serbia, as well as the global security situation, demand reestablishment of an efficient system of national security. Protection of the civilian population and material resources is particularly important in this turbulent condition, which calls for optimal development of the system of protection and rescue in accordance with the concept of total defence of the Republic of Serbia. This paper analyzes the strategic, normative and planning framework of the functioning of the system of national security (with an emphasis on the system of national defence) in the context of the contribution of the concept of total defence to the state’s resilience in emergency situations. The aim of this paper is to contribute to the understanding of the concept of total defence and strengthen its role in emergency situations by analyzing the current capabilities which must be upgraded and improved while also considering the need for the development of new capabilities. The basic hypothesis is that the development of the concept of total defence enables optimal state resilience in emergency situations. This paper also analyzes the legal and institutional framework of the concept of total defence in the context of emergency situations. Taking into account the historical heritage, this paper highlights the importance of the development of the security culture and resilience in society, which is crucial for the successful implementation of the concept of total defence. The conclusions reached by this paper point out the necessity of continuous improvement and adaptation of the system of total defence in accordance with the contemporary security challenges and needs of the Republic of Serbia.